Diets Containing Sea Cucumber (Isostichopus badionotus) Meals Are Hypocholesterolemic in Young Rats - Olivera-Castillo, Leticia; Davalos, Alberto; Grant, George; Valadez-Gonzalez, Nina; Montero, Jorge; Barrera-Perez, Hirian Alonso Moshe; Chim-Chi, Yasser; Olvera-Novoa, Miguel Angel; Ceja-Moreno, Víctor; Acereto-Escoffie, Pablo; Rubio-Piña, Jorge; Rodriguez-Canul, Rossanna (PLOS ONE, 2013)
Sea cucumber is widely consumed as a putative functional food. It contains many biologically-active substances, but only limited research on its properties in vivo has been done. The effects of different meals containing Isostichopus badionotus, a sea cucumber from southeast Mexico, on growth performance and body lipid profile in young rats were analyzed. Sea cucumber body wall was either lyophilized, cooked (100 °C, 1 h in water) and lyophilized, or oven-dried (70 °C for 12 h). It was then ground and incorporated into cholesterol-containing diets. I. badionotus meals supported growth and improved lipid profile in rats. In particular, serum cholesterol, low density lipoproteins, triglycerides concentration and atherogenic index values were greatly reduced by some I. badionotus containing diets. Liver total lipids, triglycerides and cholesterol were also reduced. Cooking or heat-treatment of the meals lowered but did not abolish their hypolipidemic potency. Gene expression analysis of several key genes involved in cholesterol and lipid metabolism in liver showed that diets containing I. badionotus repressed the induction of key genes associated with dyslipidemia exerted by cholesterol supplementation. Consumption of I. badionotus from the Yucatan Peninsula is beneficial for dyslipidemia, although biological effect is clearly dependent on preparation method.